STUDI TENTANG BRAND LOYALITY ( LOYALITAS MEREK ) PRODUK PELEMBAB POND’S ( Studi Pada Warga Perum. Bumi Citra Fajar Sidoarjo Jawa Timur) - Masitha, Raya; Yoestini, Yoestini (Faculty of Economics and Business Diponegoro University, 2013)
Currently, the competition among cosmetic producers in Indonesia is more glowing, Many cosmeticproducers in Indonesia are competing to make the qualified facial moisture product and it admissible to woman kind. The brand product of Pond’s as a market leader of facial moisture in Indonesia is gretting market share decline result from thearrival of competitors those doesn’t inferior. Pond’s was do action in order to all consumers remains loyal to this brand. The research aims to analyze the effect of factor of brand, company, and consumer brand characteristic. Respondent who imvoled within the research is 100 female; method uses non probability sampling, which is accidental sampling. Data collecting is done by distributing questionnaire and data analysis method is performed by multiple linier regression uses SPSS software. The result of regression test demonstrates company,s characteristic variable has a positive and significant effect on brand loyalty of Pond,s facial moisture 0,373. Product brand,s characteristic variable has a positive and significant effect on brand loyalty of Pond’s facial moisture 0,296. Determination coefficient value is 0.521 , it means that brand loyalty is influenced by characteristic variable of brand, company, and costumer-brand 52,1% , where asa the balance is 48,9% can be clarified by other variable those do not examined within this research.